2015
DOI: 10.1183/20734735.007915
|View full text |Cite
|
Sign up to set email alerts
|

Managing asthma in pregnancy

Abstract: Asthma is a common comorbidity during pregnancy and its prevalence is increasing in the community. Exacerbations are a major clinical problem during pregnancy with up to 45% of women needing to seek medical help, resulting in poor outcomes for mothers and their babies, including low birth weight and preterm delivery. The goals of effective asthma management in pregnancy are to maintain the best possible asthma control and prevent exacerbations. This is achieved by aiming to prevent day- and night-time symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
68
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 42 publications
2
68
0
5
Order By: Relevance
“…Furthermore, some pre-existing chronic diseases are known to worsen during pregnancy. Studies found that the rate of hospitalizations for asthma is higher among pregnant women than non-pregnant women, after adjusting for age and exacerbation history (34,35). It is also recognised that even women with mild asthma are at increased risk of severe exacerbation during pregnancy (34).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some pre-existing chronic diseases are known to worsen during pregnancy. Studies found that the rate of hospitalizations for asthma is higher among pregnant women than non-pregnant women, after adjusting for age and exacerbation history (34,35). It is also recognised that even women with mild asthma are at increased risk of severe exacerbation during pregnancy (34).…”
Section: Discussionmentioning
confidence: 99%
“…The asthma medications are safe during pregnancy and are FDA pregnancy category B and C. Upto 45% of females get moderate to severe asthma exacerbation during pregnancy [2]. Exacerbations are more severe and more frequent in patients with uncontrolled or partially controlled asthma.…”
mentioning
confidence: 99%
“…Exacerbations are more severe and more frequent in patients with uncontrolled or partially controlled asthma. Pregnant females have higher chances (1.3%) of requiring hospitalization for asthma exacerbation than non-pregnant females (0.8%) [2]. Bronchial asthma exacerbation increases the risk of perinatal complications with females with moderate to severe asthma having increased risk of preterm delivery (RR -1.54) and Low birth weight (RR -3.02) [4,5].…”
mentioning
confidence: 99%
See 2 more Smart Citations